Characterization of liquid organic fertilizer (LOF) derived from unmarketable vegetables and fruits - Ramarao, Sanjeev; Azman, Elisa Azura; Tajidin, Nor Elliza; Ismail, Roslan; Yahya, Borhan (Universiti Putra Malaysia Press, 2024)
The Malaysian government has been challenged with handling unmarketable vegetables and fruit waste that pollutes the environment and emits greenhouse gases, mainly methane and nitrous oxide. These greenhouse gases have been contributing to climate change. In contrast, these wastes consist of high moisture and readily biodegradable nutrients that can serve as the perfect substrate rate for fermentation. The valuable nutrients contained in these wastes can produce liquid organic fertilizers (LOF), which help improve the soil’s physical, chemical, and biological characteristics and reduce the demand for inorganic fertilizers and costs to farmers. In this regard, a study was conducted to produce and characterize LOF derived from unmarketable vegetables and fruit waste. The waste was identified from the nearest wet market, collected, and incubated in containers with a ratio of 1: 2: 0.1 (10 kg unmarketable vegetable and food waste: 20 L water: 1 kg inducer) for 30, 45, and 60 days. The unmarketable vegetables and fruits were fermented using three different types of inducers: yeast (Y), brown sugar (BS), and shrimp paste (SP). Unmarketable vegetables and fruit waste with no inducer were also included as a control. Samples from the produced LOF were taken after 30, 45, and 60 days of fermentation, filtered, and subjected to analysis for pH, electrical conductivity (EC), macro-, and micronutrients. These experiments were laid out in a randomized complete block design (RCBD) with three replications. The highest nitrogen (0.95%), phosphorus (0.31%), potassium (1.68%), copper (0.23 ppm), and manganese (9.03 ppm) were obtained from LOF fermented for 60 days using yeast, indicating that it improved the nutrient availability of agricultural waste. Moreover, this treatment provided optimum pH and EC values for the growth and development of plants. Thus, LOF derived from unmarketable vegetable and fruit waste can be considered an attractive alternative for supplementing chemical fertilizers.